Elementi del dramma antico nell’opera Pescatori di Raffaele Viviani: Delineazione della questione - Sterna, Marta (Verbum – Analecta Neolatina, 2018)
The ancient Greek drama after so many centuries has still been an indisputable source of inspiration for contemporary European playwrights, including those from Italy. Raffaele Viviani, regarded as one of the most prominent authors of the Neapolitan theatre in the 20th century, together with his work Pescatori (The Fishermen), published in 1925, can be a perfect example of it. The work is a unique research material with regard to its connections to antiquity. It is rich in elements that are not only related to the tradition of Greek drama but also, in certain cases, mirror its classical patterns. The aim of this article is to point to those inspirations. Due to the fact that the subject has not been discussed in any scientific publication and, taking into account that it is a very extensive question deserving to be analysed in detail, this article outlines the matter and points to further directions in terms of the research subjects that I undertook.